2006
DOI: 10.3176/oil.2006.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Technogenic Water in Closed Oil Shale Mines

Abstract: The present paper is based on the results of the research conducted in 2004 by the Department of Mining of the Tallinn University of Technology and Estonian Oil Shale Company. The state of the technogenic water body that has formed in the central part of the oil shale deposit is analysed: the water level in the area of the stopped and closed mines, water amount and movement direction, water quality and its changes. The state of the water is assessed and predicted using modelling of the water tables, statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Quality studies of mine water have shown that in about five years after the closure of a mine the content of sulfates and iron decreases below the maximum permitted level in drinking water. The highest permitted content of iron in first-class drinking water is 0.2 mg/l and that of sulfates 250 mg/l [10].…”
Section: Summary Of the Discussionmentioning
confidence: 98%
“…Quality studies of mine water have shown that in about five years after the closure of a mine the content of sulfates and iron decreases below the maximum permitted level in drinking water. The highest permitted content of iron in first-class drinking water is 0.2 mg/l and that of sulfates 250 mg/l [10].…”
Section: Summary Of the Discussionmentioning
confidence: 98%
“…In active circulation belts the temperature of water depends mostly on air temperature, while the temperature of groundwater depends on geological conditions and rock bedding depth [17]. The quality of water in closed mines improves with time as the content of sulphates and iron in the mine water decreases, gradually dropping below the maximum level permitted for drinking water within five years after mine closure [18].…”
Section: Mine Water As a Heat Sourcementioning
confidence: 99%
“…This depends on the physical properties of the porous medium, such as grain size and shape, and their arrangement and interconnection between its pores. Water permeability is largely affected by the geological disturbance of the earth's crust, which makes the aquifer highly anisotropic [18]. The permeability of rock is determined by the size of pores and cracks between its particles [19,20].…”
Section: Mine Water As a Heat Sourcementioning
confidence: 99%
See 1 more Smart Citation